Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Allium Tangerang Hotel - Basit, Abdul; Handayani, Rizky (Universitas Serang Raya, 2018)
In the current era of globalization, companies are required to have a competitive advantage in order to be able to compete and survive amid the tight of the competition. Therefore, companies need good human resources and able to compete. The background of this research is to find out whether the dimensions of service quality (tangible, reliability, assurance, responsiveness, and emphaty) affect customer satisfaction at Allium Tangerang Hotel. the goal is to find out how much the influence of the independent variable toward the dependent variable, either partially or simultaneously. This research is a quantitative-explanatory research with the research subject Allium Tangerang Hotel. The population in this study were the guests who held an event at Allium Tangerang Hotel. The samples taken were 80 respondents using purposive sampling probability technique. The results show that service quality (X), which includes five variables (Physical Evidence, Reliability, Responsiveness, Assurance, and Attention) is simultaneously related to Customer Satisfaction (Y).Keywords: Service quality, tangible, reliability, responsiveness, assurance, emphaty, customer satisfaction